2017
DOI: 10.1007/s40430-017-0839-0
|View full text |Cite
|
Sign up to set email alerts
|

Emerging application of nanoparticle-enriched cutting fluid in metal removal processes: a review

Abstract: In metal removal processes, the role of cooling and lubricating fluid is very crucial for improving the performance of machining. When metallic and non-metallic nanoparticles (less than 100 nm) are added to the base fluid, it is termed as a nanofluid. Due to excellent heat-carrying capacity, lubrication and rheological properties, nanofluids have gained immense importance for growing research activities. Researchers are also exploring synthesis and newer application of nanofluids. In the process, scientists ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 177 publications
0
19
0
Order By: Relevance
“…Furthermore, Singh et al [10] and Kishawy et al [11] studied the machining performance using MQL and concluded that using MQL technique surface nish and tool life improved and machining temperature, cutting forces are reduced. Ganguli et al [12] investigated the machining performance of Automized cutting uid spray system during machining of Titanium Alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Singh et al [10] and Kishawy et al [11] studied the machining performance using MQL and concluded that using MQL technique surface nish and tool life improved and machining temperature, cutting forces are reduced. Ganguli et al [12] investigated the machining performance of Automized cutting uid spray system during machining of Titanium Alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Behera et al [9] proposed a model for local coe cient of friction as a function of MQL parameters and cutting conditions that predicts cutting forces, contact length and chip thickness under MQL environment. Furthermore, Singh et al [10] and Kishawy et al [11] studied the machining performance using MQL and concluded that using MQL technique surface nish and tool life improved and machining temperature, cutting forces are reduced. Ganguli et al [12] investigated the machining performance of Automized cutting uid spray system during machining of Titanium Alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the cutting force decrease and the wearing of tool is reduced on account of the lubrication of atmospheric molecules. Singh [20] researched the influence of nano-particle cutting fluid on metal removal process. Wang [21] discussed the effect of water molecules on tribological behavior and property measurements in nano-indentation processes and found that the participation of water molecules makes the initial indentation force increases and the biggest indentation force decrease.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that surface roughness, cutting force, thrust force and feed force were considerably reduced. It was observed in paper [26] that inclusion of copper oxide in water during turning process reduces temperature and improves the life of the tool. In paper [27], the impact of alumina-graphene as hybrid nano fluid reduced flank wear and temperature in turning AISI 304.…”
Section: Introductionmentioning
confidence: 99%